Evaluation and Optimization of Blood Micro-Sampling Methods: Serial Sampling in a Cross-Over Design from an Individual Mouse - Nita J Patel; Enaksha Wickremsinhe; Yu-Hua Hui; Alexandar Barr; Nicholas Masterson; Kenneth Ruterbories; Jennifer Weller; Jennifer Hanes; Tom Kern; Everett Perkins (Journal of Pharmacy & Pharmaceutical Sciences, 2016)
Purpose: Current practices applied to mouse pharmacokinetic (PK) studies often use large numbers of animals with sporadic or composite sampling that inadequately describe PK profiles.  The purpose of this work was to evaluate and optimize blood microsampling techniques coupled with dried blood spot (DBS) and LC-MS/MS analysis to generate reliable PK data in mice.  In addition, the feasibility of cross-over designs was assessed and recommendations are presented. Methods: The work describes a comprehensive evaluation of five blood microsampling techniques (tail clip, tail vein with needle hub, submandibular, retro-orbital, and saphenous bleeding) in CD-1 mice.  The feasibility of blood sampling was evaluated based on animal observations, ease of bleeding, and ability to collect serial samples.  Methotrexate, gemfibrozil and glipizide were used as test compounds and were dosed either orally or intravenously, followed by DBS collection and LC-MS/MS analysis to compare PK with various bleeding methods. Results: Submandibular and retro-orbital methods that required non-serial blood collections did not allow for inter-animal variability assessments and resulted in poorly described absorption and distribution kinetics.  The submandibular and tail vein with needle-hub methods were the least favorable from a technical feasibility perspective.  Serial bleeding was possible with cannulated animals or saphenous bleeding in non-cannulated animals. Conclusions:  Of the methods that allowed serial sampling, the saphenous method when executed as described in this report, was most practical, reproducible and provided for assessment of inter-animal variability.  It enabled the collection of complete exposure profiles from a single mouse and the conduct of an intravenous/oral cross-over study design.  This methodology can be used routinely, it promotes the 3Rs principles by achieving reductions in the number of animals used, decreased restraints and animal stress, and improved the quality of data obtained in mouse PK studies.